2020
DOI: 10.1371/journal.pone.0231122
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect effects of land-use intensity on plant communities across elevation in semi-natural grasslands

Abstract: Grassland biodiversity is vulnerable to land use change. How to best manage semi-natural grasslands for maintaining biodiversity is still unclear in many cases because land-use processes may depend on environmental conditions and the indirect effects of land-use on biodiversity mediated by altered abiotic and biotic factors are rarely considered. Here we evaluate the relative importance of the direct and indirect effects of grazing intensity on plant communities along an elevational gradient on a large topogra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…Our overall assessment found that elevations negatively impact LUI with an SRC value of −0.033, implying that cities with higher elevations restrict efficient land use and thus the product from land-we use the indicator STGRPP (second and tertiary gross regional product per km 2 , unit: CNY 10,000 per km 2 ) as the proxy for the output from land to reflect the degree of LUI. Our findings of the impact of elevations agree with previous findings [30,62,63].…”
Section: The Temporal Influence Assessmentsupporting
confidence: 93%
“…Our overall assessment found that elevations negatively impact LUI with an SRC value of −0.033, implying that cities with higher elevations restrict efficient land use and thus the product from land-we use the indicator STGRPP (second and tertiary gross regional product per km 2 , unit: CNY 10,000 per km 2 ) as the proxy for the output from land to reflect the degree of LUI. Our findings of the impact of elevations agree with previous findings [30,62,63].…”
Section: The Temporal Influence Assessmentsupporting
confidence: 93%
“…Ultimately, vertical zone boundaries such as forest and snow lines will be higher in the center of the mountain system than at the periphery. In addition, Buzhdygan et al [85] suggested that human grazing practices on grassland ecosystems could become more obvious with increasing elevation, which may lead to the severe spatial fragmentation of the landscape [86]. Reclamation and deforestation in high mountains in order to meet food and timber needs will result in highly vulnerable regional landscapes [87][88][89].…”
Section: How Elevation Impacts LVI and Lhaimentioning
confidence: 99%
“…This can be explained by the tendency of mountain grasslands to have leptosol soils, highly variable slopes as well as higher elevation and lower atmospheric pressure, leading to higher precipitation and lower temperatures (Gommes, 2002;Anjos et al 2015). These conditions are known to often cause an increase in plant species richness and cover (Speed et al 2013;Buzhdygan et al 2020). In addition, Pando- Moreno et al (2013) found that many of the sites in mountain grasslands within GPCA El Tokio had a lower level of electrical conductivity and absence of gypsum, while sites that fall within calcareous, arid and agricultural grassland types had at least some percentage of gypsum in them.…”
Section: Discussionmentioning
confidence: 99%